2020
DOI: 10.1016/j.midw.2020.102821
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from past epidemics and pandemics and a way forward for pregnant women, midwives and nurses during COVID-19 and beyond: A meta-synthesis

Abstract: Highlights The experiences of pregnant women from past epidemics and pandemics were consolidated. Midwives’ and nurses’ perceptions of epidemics and pandemics were explored. Individualized and contextualized educational support is needed. Culturally congruent care and emotional and financial support need to be prioritized. Healthcare professionals can consider technology-based and community-led supportive programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 45 publications
6
51
0
3
Order By: Relevance
“…The emotions described by the interviewed participants ranged from fear to uncertainty, and also included worry and anxiety; we find a similar scenario in the meta-analysis of Shorey and Chan [ 28 ], which describes the negative psychological responses experienced by midwives and nurses during the pandemic, although it was observed that the family occupied a fundamental role in terms of providing support to the professionals. In our case, the family has occasionally been a source of worry for the midwives who witnessed members of their family taking ill or who saw how their partner had to stay in a hotel away from the home for fear of infecting the interviewed midwife who was pregnant.…”
Section: Discussionsupporting
confidence: 69%
“…The emotions described by the interviewed participants ranged from fear to uncertainty, and also included worry and anxiety; we find a similar scenario in the meta-analysis of Shorey and Chan [ 28 ], which describes the negative psychological responses experienced by midwives and nurses during the pandemic, although it was observed that the family occupied a fundamental role in terms of providing support to the professionals. In our case, the family has occasionally been a source of worry for the midwives who witnessed members of their family taking ill or who saw how their partner had to stay in a hotel away from the home for fear of infecting the interviewed midwife who was pregnant.…”
Section: Discussionsupporting
confidence: 69%
“…As highlighted by participants in this study, the systems in place did not adequately support patients or the nurses caring for them, and efforts are needed to make sure that changes at the systems levels have the health and wellbeing of both patients and nurses in mind. All system changes should be tailored to address the needs of pregnancy and birth care and to assure that the impacts from these changes are equitable ( Shorey & Chan, 2020 ). This pandemic will continue to have lasting impact on pregnant and birthing families, and the nurses who care for them, and it is imperative that hospitals examine their role and any potential impacts.…”
Section: Discussionmentioning
confidence: 99%
“…Human civilizations have experienced various severe health problems because of the changes in the standard quality of earth, water, sky, air, and fire, which adversely affected humans' wellbeing and health in different societies worldwide. [1][2][3][4][5] Since civilizations' birth, humans encountered various epidemics and pandemics, which caused panic, destruction, morality, and mental health issues. [6][7][8][9] The outbreak of epidemics affects regions, while the pandemics effects are global and cause adverse consequences in spreading diseases.…”
Section: Introductionmentioning
confidence: 99%